2023
DOI: 10.1021/acscatal.3c00432
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Rotating Disk Electrode Study of Platinum Bimetallic Catalysts in Phosphoric Acid

Abstract: Understanding the H3PO4 effect on the catalyst’s activity under a relevant condition is important for high-temperature polymer electrolyte membrane fuel cell (HT-PEMFC) catalyst research. Here, we report a high-temperature rotating disk electrode (HT-RDE) study of oxygen reduction reaction (ORR) in H3PO4. With the regular electrochemical protocol, we found that H3PO4 reduction could occur during cyclic voltammetry study and form a reductive speciesphosphorus acid (H3PO3). To obtain reliable ORR measurement, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…15d and e). 80 Under conventional electrochemical schemes, it was observed that the reducing substance PA (H 3 PO 3 ) undergoes oxidation by H 3 PO 4 reduction during cyclic voltammetry (CV) cycles. In order to obtain reliable ORR measurements, the testing plan was optimized to avoid the formation of H 3 PO 3 .…”
Section: High-temperature Rotating Disk Electrode Study Of Catalysts ...mentioning
confidence: 99%
“…15d and e). 80 Under conventional electrochemical schemes, it was observed that the reducing substance PA (H 3 PO 3 ) undergoes oxidation by H 3 PO 4 reduction during cyclic voltammetry (CV) cycles. In order to obtain reliable ORR measurements, the testing plan was optimized to avoid the formation of H 3 PO 3 .…”
Section: High-temperature Rotating Disk Electrode Study Of Catalysts ...mentioning
confidence: 99%